Pure and Applied Chemistry:9th eurasia conference on chemical sciences - Guide to IUPAC; Sener,Bilge (Turkey, 2006)
Official journal of the international union of pure and applied chemistry
Vol.79,No.12,December 2007
Keywords: Chemistry; chemical science